2021
DOI: 10.22175/mmb.11626
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Factors Affecting East Asian Consumers’ Sensory Preferences of Six Beef Shank Cuts

Abstract: The objective of this study was to evaluate biochemical factors affecting Warner-Bratzler shear force (WBSF) and East Asian consumers’ eating preferences of 6 different beef shank cuts cooked by moist heat. Six different beef shank muscles were collected from 12 USDA Choice beef carcasses (N = 72). Shank cuts from the left sides were cooked with moist heat and used for East Asian consumer sensory evaluation and WBSF, and shank cuts from the right sides were left uncooked and used for biochemical analysis and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…Ueda et al (2007) further corroborated this postulation, wherein they found a negative correlation between fat content and shear force values (r = −0.83) in the loins of Wagyu cattle, a breed known for its high levels of marbling. On the other hand, the findings of the current study agreed with Chun et al (2020), who found an inverse relationship between collagen content and overall tenderness (r = −0.42), and Wu et al (2021) and Zimmerman et al (1993), who both found mature collagen crosslink density had a positive correlation with different types of mechanical stress measurement. Finally, this is the first study to the authors' knowledge that reported a statistically significant correlation between overall tenderness and DPD density for GM.…”
Section: Correlation Coefficients and Multivariate Regression Modelssupporting
confidence: 91%
See 2 more Smart Citations
“…Ueda et al (2007) further corroborated this postulation, wherein they found a negative correlation between fat content and shear force values (r = −0.83) in the loins of Wagyu cattle, a breed known for its high levels of marbling. On the other hand, the findings of the current study agreed with Chun et al (2020), who found an inverse relationship between collagen content and overall tenderness (r = −0.42), and Wu et al (2021) and Zimmerman et al (1993), who both found mature collagen crosslink density had a positive correlation with different types of mechanical stress measurement. Finally, this is the first study to the authors' knowledge that reported a statistically significant correlation between overall tenderness and DPD density for GM.…”
Section: Correlation Coefficients and Multivariate Regression Modelssupporting
confidence: 91%
“…It was also peculiar that the panelists perceived RA to have one of the highest connective tissue amounts, considering it has one of the lowest collagen contents according to the biochemical analysis. Wu et al (2021) found that mature collagen crosslink PYD is heat stable, and as PYD density increases, the overall solubility of collagen decreases. Consequently, this results in a tougher connective tissue texture in cooked meat products, which may explain the high amount of connective tissue detected by the trained panels in PP and RA.…”
Section: Trained Sensory Panel and Warner-bratzler Shear Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Although the correlations between collagen content and solubility and tenderness attributes were weak, the increase in the density of heat-stable collagen cross-links was positively related to increasing toughness, which was also shown by several studies (Listrat et al, 2020;Wang et al, 2016;Wu et al, 2021). However, McCormick (1999 reported that increased density of pyridinoline cross-link was related to increased collagen solubility and WBSF.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, the scar tissue and fibrosis in WB filets could potentially be leading to the promotion of high densities of collagen crosslinking. Finally, Wu et al (2021) documented a strong positive correlation between PYD density in raw beef shank cuts and WBSF and connective tissue texture evaluated by East Asian consumers. It is likely the increase in mature collagen crosslink density may contribute to the rubbery texture and increased thermal denaturation temperature of the connective tissue observed in WB samples from this study.…”
Section: Resultsmentioning
confidence: 83%